Diffusiophoretic enhancement of mass transfer by nanofluids. (2nd February 2018) - Dhuriya, Rakhi; Dalia, Varun; Sunthar, P.
Graphical abstract: Highlights: Mass transfer enhancement by nanofluids is demonstrated in a capillary tube. The enhanced motion of the solute is shown to be due to diffusiophoresis. Diffusiophoresis of nanoparticles induces a counter-convective motion of the dye. Earlier observations of mass transfer effects in nanofluids explained. Abstract: Observations of an enhanced mass transfer and an irregular mixing when a small drop of dye is gently placed on a nanofluid dispersion have led to several propositions for the underlying cause, but none of them have been conclusively established. Here, we reproduce the enhancement phenomenon within a glass capillary containing fluorescein di-sodium dye solution on one side and alumina nanoparticle suspension on the other, avoiding the inertial interference present earlier. The enhancement is explained by the convective motion (and not a diffusion) of the dye solution counter to the direction of the diffusiophoretic motion of the nanoparticles towards a higher concentration of the dye. The initial velocity of the dye front in the capillary and the dye-drop experiment agree quantitatively with independent theoretical estimates from the diffusiophoretic velocity of alumina nanoparticles. With a suitably chosen nanofluid, it should now be possible to effect a desired level of enhancement (or suppression) of mass transfer of any solute. In micro-environments requiring fast mixing, such as in nanofabrication, lab-on-chip, drug-delivery, and chemotaxis, the effects can be substantial.